Pragmatismo contra normativismo: investigações sobre a teoria política de Carl Schmitt - Lima, Deyvison Rodrigues (2011)
This dissertation proposes the reconstruction of Schmitt’s thesis about the modern distinction between facticity and validity in the field of political theory. The purpose is to analyse the modern political paradigms – normative and realism – as a consequence of the problematic relationship between immediate and mediate in the political way. The hypothesis is (I) if on the one hand Schmitt’s political theory arises in opposition to the normative model, on the other it cannot be applied to the political realism – be it strong or weak – meaning an alternative theoretical proposal in the face of the rationalist mediation; therefore (II) it’s necessary to scrutinize what are the essential characteristics of the Schmittian project of restructuring of the political theory paradigm developed, generally speaking, in three distinct moments of the discussion: the first articulated by means of the notion of Entscheidung and later developed within the scope of the Theory of Exception; the second called political existentialism; and the third developed from the theory of nomos. The main findings of this research are the demonstration of Schmitt undertakes an attempt of reorganize the modern political paradigms in the face of the problem of the mediation between “being” and “ought to be”, and the possibility that the author developed the thesis of there is possible mediation, but only the immediateness of a legal force does not mediated by laws, in other words, a real and legal institutional fact between the universal and the particular by means of which needs no necessity of a normative theory of justification of law (legitimacy), for the Sein is even now, and first of all, a social reality mediated and constitued legally, hence, the legitimacy should be understood as historical and real demonstrating the cooriginality between “being” and “ought to be”, and, finally, solving the mediate/immediate paradox by means to a political pragmatism.